The role of the excitation:inhibition functional balance in the mPFC in the onset of antidepressants. (15th June 2021) - Yin, Yong-Yu; Wang, Yun-Hui; Liu, Wen-Gang; Yao, Jun-Qi; Yuan, Jin; Li, Ze-Han; Ran, Yu-Hua; Zhang, Li-Ming; Li, Yun-Feng
Abstract: Currently available antidepressants, such as selective serotonin reuptake inhibitors (SSRIs) and serotonin and norepinephrine reuptake inhibitors (SNRIs), generally require weeks to months to produce a therapeutic response, but the mechanism of action underlying the delayed onset of antidepressant-like action remains to be elucidated. The balance between excitatory glutamatergic pyramidal neurons and inhibitory γ-aminobutyric acid (GABA) interneurons, i.e., the excitation:inhibition functional (E:I) balance, in the medial prefrontal cortex (mPFC) is critical in regulating several behaviors and might play an important mediating role in the mechanism of rapid antidepressant-like action reported by several studies. In the present study, the multichannel electrophysiological technique was used to record the firing activities of pyramidal neurons and interneurons and investigate the effects of a single dose of fluoxetine and ketamine (both 10 mg/kg, i.p.) on the E:I functional balance in the rat mPFC after 90 min or 24 h, and the forced swimming test (FST) was used to evaluate the antidepressant-like effects of fluoxetine and ketamine. The present study also explored the effects of chronic treatment with fluoxetine (10 mg/kg, i.g.) for 7 d or 21 d on the E:I functional balance in the mPFC. The present results suggested that a single dose of ketamine could both significantly increase the firing activities of pyramidal neurons and significantly decrease the firing activities of interneurons in the mPFC and exerted significant antidepressant-like action on the FST after 90 min and 24 h, but fluoxetine had no such effects under the same conditions. However, chronic treatment with fluoxetine for 21 d (but not 7 d) could significantly affect the firing activities of pyramidal neurons and interneurons in the mPFC. Taken together, the present results indicated that rapid regulation of the E:I functional balance in the mPFC might be an important common mechanism of rapid-acting antidepressants and the delayed onset of SSRIs might be partly attributed to their inability to rapidly regulate the E:I functional balance in the mPFC. The present study provided a new entry point to the development of rapid-acting antidepressants. Highlights: The E:I balance might be a dynamic balance and the levels of E:I balance indicate different antidepressant-like effects. The E:I balance in the mPFC might be an important pharmacological target with rapid-acting antidepressant-like effects. The delayed onset of SSRIs could be attributed to their inability to rapidly regulate the E:I balance in the mPFC.